PEMANFAATAN PELAYANAN KESEHATAN DI POSYANDU LANSIA WILAYAH KERJA PUSKESMAS TUALANG KABUPATEN SIAK - Erna Widyawati; Jasrida Yunita; Novita Rany; Hetty Ismainar; Ahmad Hanafi (LPPM Universitas Abdurrab, 2024)
In Indonesia, visits to elderly posyandu (integrated health service posts) are generally below target, particularly in Siak Regency, Riau Province, where elderly health services have been declining annually, especially at Tualang Health Center. This study aims to understand elderly behavior in utilizing health services through knowledge, attitudes, actions, and health center efforts. This qualitative study employs a phenomenological design and was conducted in the working area of Tualang Health Center, Siak Regency, from March to May 2024. The total number of informants is 24, consisting of 9 main informantsÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬Â3 active elderly (AE) who visit posyandu monthly, 3 inactive elderly (IE) who missed posyandu visits three times a year, and 3 non-attending elderly (NE) who never visit posyandu. Additionally, there are 15 supporting informants, including family members, the head of the health center, elderly program managers, midwives, and 3 cadres. Data processing utilized data triangulation and thematic analysis. The study found that AE and IE have better knowledge compared to NE due to their participation in posyandu activities. All elderly informants had a positive attitude towards the quality of health services at posyandu. AE tend to visit posyandu regularly due to easy access, transportation, and family support, while IE and NE are less active due to distant access, limited transportation, and lack of family support. It is recommended that the health center empower elderly families to increase elderly participation in utilizing health services.